Rubber material, synchronous belt and preparation method and application of synchronous belt

By optimizing the rubber material of the formula, the problem of micro synchronous belts being easy to fold and bend and degraded during production and use is solved, and the synchronous belt with high tensile strength, excellent antistatic properties and long service life is achieved, which meets environmental protection and Requirements for high-precision equipment.

CN119490702APending Publication Date: 2025-02-21NINGBO YUJIANG SPECIAL TAPE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411636025.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing micro-synchronous belts are susceptible to folding and bending during production and use, resulting in reduced performance and shortened service life, while difficult to meet environmental standards and high-precision electronic equipment's requirements to combat static electricity.

Method used

Using optimized formulation rubber materials, including neoprene, butylene rubber, anti-coke agent, reinforcement, promoter, anti-aging agent, dispersing agent, plasticizer, crosslinking agent and tackifier, by replacing the contaminating group The plasticizing and tackifying system is optimized to improve the tensile strength, antistatic properties and adhesion of rubber materials.

Benefits of technology

It significantly improves the tooth shear strength, anti-flexural fatigue performance, anti-static performance and service life of the synchronization belt, meets the long-term use needs of computer optometry instruments for synchronization belts, and meets environmental protection standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a rubber material, a synchronous belt and a preparation method and application thereof, and relates to the technical field of synchronous belts. The rubber material comprises the following raw materials: 95-100 parts of chloroprene rubber, 0.1-5 parts of butadiene rubber, 6-9 parts of a scorch retarder, 51-63 parts of a reinforcing agent, 0.2-0.5 part of an accelerant, 3-5 parts of an anti-aging agent, 4-6 parts of a dispersant, 5-7 parts of a plasticizer, 4-6 parts of a cross-linking agent and 4.5-6 parts of a tackifier, the accelerant comprises 3-methyl-2-thiazolethione, the plasticizer comprises dioctyl sebacate and oligomer ester, the anti-aging agent comprises 4, 4 '-diethylhexyl sebacate, and the cross-linking agent comprises 4, 4'-diethylhexyl sebacate. The reinforcing agent comprises carbon black, multiwalled carbon nanotubes and precipitated white carbon black, and the tackifier comprises hexamethylol melamine hexamethyl ether and coumarone resin. The prepared synchronous belt has the advantages of good antistatic performance, long service life, environmental protection and the like, and can meet the requirements of the synchronous belt for the computer optometry unit on environmental protection performance and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of synchronous belts, and in particular to a rubber material, a synchronous belt, and a preparation method and application thereof. Background Art

[0002] Computer ophthalmometer is an advanced medical device used to objectively check the refractive state of the eyeball. Its core lies in accuracy and efficiency. Computer ophthalmometer uses a variety of precision mechanical and electronic control systems inside, among which micro timing belts play a key role. Micro timing belts are mainly used to transmit power and achieve precise motion control. In computer ophthalmometer, timing belts can drive various moving parts, such as lenses, gratings and detection probes, to ensure their smooth and precise movement during operation.

[0003] In the face of increasingly stringent environmental standards, especially the regulations of ROHS and REACH, the micro timing belts used in computer ophthalmometers must meet environmental standards. In view of the fact that the timing belt is easily affected by folding and bending during production and use, which weakens its performance and shortens its life, it is necessary to improve its flexibility and fatigue resistance. In addition, since the computer ophthalmometer is a high-precision electronic device with complex integrated circuits inside, this requires the timing belt to have excellent anti-static properties to ensure the safe operation of the equipment. In summary, in order to meet environmental protection requirements, extend service life and ensure equipment safety, it is particularly important to improve the material and performance of micro timing belts. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a rubber material, a synchronous belt, and a manufacturing method and application thereof. The rubber material has the advantages of high tensile strength, strong antistatic performance, high adhesion and green environmental protection. The synchronous belt prepared using the rubber material has the advantages of high tooth shear strength, excellent flexural fatigue resistance, good antistatic performance, long service life and green environmental protection.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a rubber material, wherein the raw materials of the rubber material include the following components in parts by mass: 95-100 parts of chloroprene rubber, 0.1-5 parts of butadiene rubber, 6-9 parts of scorch retarder, 51-63 parts of reinforcing agent, 0.2-0.5 parts of accelerator, 3-5 parts of antioxidant, 4-6 parts of dispersant, 5-7 parts of plasticizer, 4-6 parts of crosslinking agent and 4.5-6 parts of tackifier, wherein the accelerator includes 3-methyl-2-thiazolethione, the plasticizer includes dioctyl sebacate and oligomeric esters, the antioxidant includes 4,4'-dioctyldiphenylamine, the reinforcing agent includes carbon black, multi-walled carbon nanotubes and precipitated silica, and the tackifier includes hexahydroxymethylmelamine hexamethylene ether and coumarone resin.

[0006] The present invention replaces polluting components in the formula of the existing rubber material with non-polluting components, replaces the polluting component accelerator ethylene thiourea (ETU) with 3-methyl-2-thiazolethione, replaces the plasticizer dioctyl phthalate (DOP) with dioctyl sebacate (DOS) and oligoesters, and replaces the antioxidant 4-isopropylaminodiphenylamine (4010NA) with 4,4'-dioctyldiphenylamine (ODA), thereby significantly reducing the pollutant content in the rubber material and improving the environmental protection performance of the rubber material and the synchronous belt; at the same time, by using carbon black, multi-walled carbon nanotubes and precipitated silica as reinforcing agents and using hexahydroxymethyl melamine hexamethylenetetramine and coumarone resin as adhesives in the formula of the rubber material, the rubber material has the advantages of high tensile strength, strong antistatic performance, strong adhesion with the tooth surface protective layer canvas and the glass core rope, and green environmental protection.

[0007] In a possible embodiment, the mass ratio of the dioctyl sebacate and the oligoester in the plasticizer is 1:(1-3). The use of dioctyl sebacate and oligoester as plasticizers can reduce polluting components while also utilizing the oligoester to play a plasticizing role before vulcanization, and to play a hardening and reinforcing role after vulcanization, thereby improving the plasticity and strength of the rubber material; by optimizing the ratio of dioctyl sebacate and oligoester, the rubber material can have both excellent plasticity and strength.

[0008] In a possible implementation, the mass ratio of the carbon black, the multi-walled carbon nanotubes and the precipitated silica in the reinforcing agent is (50-58):(1-5):(4.5-6). By optimizing the ratio of carbon black, multi-walled carbon nanotubes and precipitated silica, the resistivity of the rubber material is reduced, the antistatic property of the rubber material is improved, and the rubber material also has a higher tensile strength.

[0009] In a possible implementation, the mass ratio of the hexamethylol melamine hexamethylol ether to the coumarone resin in the tackifier is 1:(1-4). By optimizing the ratio of hexamethylol melamine hexamethylol ether to the coumarone resin, the adhesion between the rubber material and the covering layer and the glass core rope can be enhanced.

[0010] In a possible embodiment, the scorch retarder includes one or more of magnesium oxide and layered double metal hydroxide. The scorch retarder can extend the scorch time and widen the scorch temperature range, and can also be combined with a cross-linking agent to control the cross-linking time to be appropriate, which is convenient for processing and operation, and can save costs and energy consumption.

[0011] In a possible implementation, the accelerator includes 3-methyl-2-thiazolethione. The use of the above accelerator is more conducive to shortening the vulcanization time and reducing the vulcanization temperature.

[0012] In a possible implementation, the dispersant includes a surfactant, a fatty acid soap and polyvinyl alcohol. The surfactant, fatty acid soap and polyvinyl alcohol are used as dispersants, and other ingredients can be combined to improve the uniformity of the rubber material and improve the consistency of product quality.

[0013] In a possible implementation, the cross-linking agent includes zinc oxide. Using zinc oxide as a cross-linking agent can make the rubber material have higher strength and elasticity.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned rubber material, comprising the following steps: F1, chloroprene rubber and butadiene rubber are plasticized to obtain a mixed plasticized rubber; F2, adding a dispersant, a plasticizer, a scorch retarder and a reinforcing agent to the mixed plasticized rubber in step F1, mixing and draining the rubber, wherein the plasticizer is dioctyl sebacate and oligomeric esters, and the reinforcing agent includes carbon black, multi-walled carbon nanotubes and precipitated silica, to obtain a masterbatch; F3, in step F2, an antioxidant, an accelerator, a crosslinking agent and a tackifier are added to the first-stage masterbatch and mixed, and the rubber is discharged after the mixing is completed, the accelerator is 3-methyl-2-thiazolethione, and the tackifier is hexahydroxymethyl melamine hexamethyl ether and coumarone resin to obtain a second-stage masterbatch; F4. Extruding the second-stage masterbatch in step F3 to obtain an extruded rubber sheet, and vulcanizing the extruded rubber sheet to obtain a rubber material.

[0015] In a possible implementation, in step F1, the specific process of mastication is that the chloroprene rubber and the butadiene rubber are masticated once on an open mixing mill respectively, and then the masticated chloroprene rubber and butadiene rubber are mixed, and masticated a second time to obtain a mixed masticated rubber.

[0016] Furthermore, in step F1, the first mastication time of the chloroprene rubber is 180-210 s, the first mastication time of the butadiene rubber is 30-60 s, and the second mastication time of step F1 is 120-150 s.

[0017] In a possible implementation, in step F2, the mixing process is to add the mixed plasticized rubber obtained in step F1 into an internal mixer, then add a dispersant, a plasticizer, a scorch retarder and a flame retardant for a first mixing, then add a reinforcing agent for a second mixing and then discharge the rubber, and then cool it with cooling water and keep it warm to obtain a masterbatch.

[0018] Furthermore, in step F2, the rotor speed of the internal mixer is 30-35 r / min, the time of the first mixing is 120-150 s, the time of the second mixing is 120-150 s, and the temperature of the debinding is 100-120°C.

[0019] In a possible implementation, in step F3, the mixing process is to add the first-stage masterbatch after being insulated in step F2 into the internal mixer again, and then add an antioxidant, an accelerator, a cross-linking agent and a tackifier and mix them. After the mixing is completed, the rubber is discharged, and then cooled with cooling water and insulated to obtain a second-stage masterbatch.

[0020] Furthermore, in step F3, during the mixing, the speed of the internal mixer is 30-35 r / min, the mixing time is 70-90 s, and the debinding temperature is 90-100 °C.

[0021] In a possible implementation, in step S4, the extrusion speed is 3.7-5.3 r / min, the thickness of the extruded film is 0.65-0.75 mm, the vulcanization temperature is 160° C., the pressure is 5-10 Mpa, and the time is 28-35 min.

[0022] In a third aspect, the present invention provides a synchronous belt, comprising a rubber layer, a strength layer, a tooth rubber layer and a cloth covering layer, wherein the rubber layer and the tooth rubber layer are prepared from the above-mentioned rubber material.

[0023] The synchronous belt provided by the present invention is prepared by adopting the above-mentioned rubber material with high tensile strength, strong antistatic performance, high adhesion and green environmental protection, so that the prepared synchronous belt has the advantages of high tooth shear strength, excellent flexural fatigue resistance, good antistatic performance, long service life and green environmental protection.

[0024] In a possible implementation, the synchronous belt has a thickness of 1.14±0.2 mm and a width of 6.3±0.2 mm.

[0025] In a possible implementation, the pitch line length of the synchronous belt is 186.944±0.4 mm.

[0026] In a fourth aspect, the present invention provides a method for preparing the above-mentioned synchronous belt, comprising the following steps: S1, the elastic wrapping material is impregnated with glue and then attached to a mold, the mold has a plurality of tooth-shaped grooves, and the wrapping material is attached to the mold surface on one side of the opening of the tooth-shaped grooves; S2, after impregnation, the glass fibers are twisted again to obtain a glass core rope, a plurality of the glass core ropes are wound around the elastic wrapping material of step S1, and the rubber material is wrapped around the glass core rope; S3, pressing the rubber material so that the rubber material penetrates the glass core rope and stretches the elastic cloth material to enter the toothed groove of the mold to form the synchronous belt.

[0027] In a possible implementation, the wrapping cloth material in step S1 is nylon white grey cloth.

[0028] In a possible implementation manner, the adhesive material for the adhesive impregnation in step S1 is a slurry obtained by dissolving the above-mentioned rubber material in toluene, and the amount of adhesive attached to the stretch fabric material after the adhesive impregnation is 70-80 g / m 2 .

[0029] In a possible implementation manner, in step S2, the strand density of the glass fiber is 120-135 g / 1000m, the number of strands of the glass fiber is 3, and the impregnating solution is an RFL impregnation solution.

[0030] In a possible implementation manner, the twist of the glass core rope in step S2 is 140-160, and the tensile strength of a single glass core rope is greater than 80N.

[0031] By adopting the glass core rope, the flexural fatigue resistance of the synchronous belt can be further improved.

[0032] In a possible implementation manner, the pressing pressure in step S3 is 1-1.6 Mpa.

[0033] In a fifth aspect, the present invention also provides application of the above-mentioned synchronous belt in a computer ophthalmometer.

[0034] The above-mentioned preferred conditions can be combined arbitrarily based on the common knowledge in the art.

[0035] The reagents and raw materials used in the present invention are commercially available.

[0036] The positive and progressive effects of the present invention are: The present invention optimizes the formula of the rubber material and adopts non-polluting reagents to reduce the content of pollutants in the rubber material and improve the environmental protection performance of the rubber material and the synchronous belt; and improves the tensile strength of the rubber material and the adhesion with the tooth surface protective layer canvas and the glass core rope by improving the reinforcement system, the plasticizing system and the viscosity increasing system, and also significantly improves the tooth shear strength and flexural fatigue resistance of the synchronous belt prepared by using the rubber material, significantly improves the service life of the synchronous belt, and meets the long service life requirement of 8-10 years for the synchronous belt of the computer ophthalmometer. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0038] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0039] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0040] Example 1

[0041] The present embodiment provides a rubber material, whose raw materials include the following components in parts by weight: 98 parts of chloroprene rubber, 3 parts of butadiene rubber, 8 parts of scorch retarder, 56 parts of reinforcing agent, 0.3 parts of accelerator, 4 parts of antioxidant, 5 parts of dispersant, 6 parts of plasticizer, 5 parts of crosslinking agent and 5 parts of tackifier; the scorch retarder is magnesium oxide and layered double metal hydroxide, and the mass ratio of magnesium oxide to layered double metal hydroxide is 1:1; the accelerator is 3-methyl-2-thiazolethione; the plasticizer is dioctyl sebacate and oligomeric ester, and the mass ratio of dioctyl sebacate and oligomeric ester is 1:1. The weight ratio of the carbon black, multi-walled carbon nanotubes and precipitated silica is 50:5:5; the dispersant is a surfactant, a fatty acid soap and polyvinyl alcohol, and the weight ratio of the surfactant, fatty acid soap and polyvinyl alcohol is 2:2:1; the cross-linking agent is zinc oxide; the tackifier is hexamethylolamine and coumarone resin, and the weight ratio of hexamethylolamine and coumarone resin is 1:2.

[0042] It is prepared by the following preparation method: F1, 98 parts of chloroprene rubber were masticated for 200 s on an open mill with a roll gap of 2 mm, and 3 parts of cis-1,4-dibutyl rubber were masticated for 45 s on an open mill with a roll gap of 2 mm, and the masticated chloroprene rubber and cis-1,4-dibutyl rubber were mixed and masticated for a second time for 140 s to obtain a mixed masticated rubber; F2, the mixed plasticized rubber obtained in step F1 is added to an internal mixer, the rotor speed of the internal mixer is set to 33 r / min, and then 5 parts of dispersant, 6 parts of plasticizer and 8 parts of scorch retarder are added for primary mixing for 135 s, and then the rotor speed of the internal mixer is set to 33 r / min, and 56 parts of reinforcing agent are added for secondary mixing for 130 s, and then the glue is discharged at a temperature of 110°C, and then cooled with cooling water at 25°C, and kept at 25°C for 20 hours to obtain a masterbatch; F3, the first-stage masterbatch obtained in step F2 is added to the internal mixer again, the rotor speed of the internal mixer is set to 30 r / min, and then 4 parts of antioxidant, 0.3 parts of accelerator, 5 parts of cross-linking agent and 5 parts of tackifier are added and mixed for 80 s. After the mixing is completed, the glue is discharged at 95°C, and then it is quickly cooled by cooling water at 25°C, and then kept at 25°C for 20 h to obtain the second-stage masterbatch; F4. Add the second-stage masterbatch obtained in step F3 into an extruder and extrude to obtain an extruded rubber sheet. The extrusion speed of the extruder is 4.5 r / min, and the thickness of the extruded rubber sheet is 0.7 mm. Then, after standing at room temperature for 30 hours, the extruded rubber sheet is vulcanized at a temperature of 160° C., a pressure of 8 MPa, and a time of 30 min to obtain a rubber material.

[0043] The tensile strength of the rubber material obtained in Example 1 is 18.1 MPa.

[0044] Example 2

[0045] The present embodiment provides a synchronous belt, which includes a rubber layer, a strength layer, a tooth rubber layer and a cloth covering layer, wherein the rubber layer and the tooth rubber layer are made of the rubber material prepared in Example 1, the thickness of the synchronous belt is 1.14±0.2 mm, the width is 6.3±0.2 mm, and the pitch line length of the synchronous belt is 186.944±0.4 mm.

[0046] It is prepared by the following preparation method: S1. The rubber material prepared in Example 1 is dissolved in toluene to obtain a slurry material. A 0.3 mm thick PA66 nylon white grey cloth is impregnated with the slurry material to make the amount of adhesive on the PA66 nylon white grey cloth reach 75 g / m 2 Then, the PA66 nylon white fabric is attached to the mold, which has a plurality of tooth-shaped grooves, and the PA66 nylon white fabric is attached to the mold surface on the side of the tooth-shaped groove opening; S2, immersing three strands of glass fiber with a linear density of 127 g / 1000m in an RFL aqueous solution and then twisting them into a glass core rope, wherein the twist of the glass core rope is 150, and the tensile strength of a single glass core rope is greater than 80 N, and the plurality of glass core ropes are wound around the PA66 nylon white fabric prepared in step S1, and the rubber material prepared in Example 1 is wrapped around the glass core rope; S3. In the vulcanizing tank, the rubber material is compressed with 1.4 MPa high-pressure air, so that the rubber material penetrates the gap between the glass core ropes and stretches the PA66 nylon white fabric to enter the toothed groove of the mold to form a tooth layer and obtain a synchronous belt.

[0047] The tensile strength of the synchronous belt obtained in Example 2 is 679 N and the surface resistivity is 1×10 4 Ω·m, the synchronous belt was applied to the RM / KR-9600 computer ophthalmometer. After 35,000 lifting and lowering tests, the synchronous belt was in good condition and could meet the service life requirement of 8-10 years.

[0048] Example 3

[0049] The present embodiment provides a rubber material, whose raw materials include the following components in parts by weight: 95 parts of chloroprene rubber, 5 parts of butadiene rubber, 6 parts of scorch retarder, 63 parts of reinforcing agent, 0.2 parts of accelerator, 5 parts of antioxidant, 4 parts of dispersant, 7 parts of plasticizer, 4 parts of crosslinking agent and 6 parts of tackifier; the scorch retarder is magnesium oxide; the accelerator is 3-methyl-2-thiazolethione; the plasticizer is dioctyl sebacate and oligomeric ester, and the mass fractions of dioctyl sebacate and oligomeric ester are 1:1; the antioxidant is 4,4'- The invention discloses a novel novel nanostructured carbon fiber comprising: dioctyldiphenylamine; a reinforcing agent comprising: carbon black, multi-walled carbon nanotubes and precipitated silica, wherein the mass ratio of carbon black, multi-walled carbon nanotubes and precipitated silica is 58:1:6; a dispersant comprising: a surfactant, a fatty acid soap and polyvinyl alcohol, wherein the mass ratio of the surfactant, the fatty acid soap and polyvinyl alcohol is 4:2:3; a crosslinking agent comprising: zinc oxide; and a tackifier comprising: hexamethylolamine hexamethyl ether and coumarone resin, wherein the mass ratio of hexamethylolamine hexamethyl ether and coumarone resin is 1:1.

[0050] It is prepared by the following preparation method: F1, 95 parts of chloroprene rubber were masticated for 180 s on an open mill with a roll gap of 2 mm, and 5 parts of butadiene rubber were masticated for 60 s on an open mill with a roll gap of 2 mm, and the masticated chloroprene rubber and butadiene rubber were mixed and masticated for a second time for 120 s to obtain a mixed masticated rubber; F2, the mixed plasticized rubber obtained in step F1 is added to an internal mixer, the rotor speed of the internal mixer is set to 35 r / min, 4 parts of dispersant, 7 parts of plasticizer and 6 parts of anti-scorch agent are added to carry out primary mixing for 120 s, the rotor speed of the internal mixer is set to 35 r / min, 63 parts of reinforcing agent are added to carry out secondary mixing for 120 s, and then the glue is discharged at a temperature of 120°C, and then cooled with cooling water at 25°C, and kept at 25°C for 20 h to obtain a masterbatch; F3, the first-stage masterbatch obtained in step F2 is added to the internal mixer again, the rotor speed of the internal mixer is set to 30 r / min, and then 5 parts of antioxidant, 0.2 parts of accelerator, 4 parts of cross-linking agent and 6 parts of tackifier are added and mixed for 90 s. After the mixing is completed, the glue is discharged at 90°C, and then it is quickly cooled by cooling water at 25°C, and then kept at 25°C for 20 h to obtain the second-stage masterbatch; F4. Add the second-stage masterbatch obtained in step F3 into an extruder to extrude an extruded rubber sheet. The extrusion speed of the extruder is 3.7 r / min. The thickness of the extruded rubber sheet is 0.75 mm. Then, after standing at room temperature for 20 hours, the extruded rubber sheet is vulcanized at a temperature of 160°C, a pressure of 10 MPa, and a time of 28 min to obtain a rubber material.

[0051] The tensile strength of the rubber material obtained in Example 3 is 17.3 MPa.

[0052] Example 4

[0053] The present embodiment provides a synchronous belt, which includes a rubber layer, a strength layer, a tooth rubber layer and a cloth covering layer, wherein the rubber layer and the tooth rubber layer are made of the rubber material prepared in Example 3, the thickness of the synchronous belt is 1.14±0.2 mm, the width is 6.3±0.2 mm, and the pitch line length of the synchronous belt is 186.944±0.4 mm.

[0054] It is prepared by the following preparation method: S1. The rubber material prepared in Example 3 is dissolved in toluene to obtain a slurry material. A 0.3 mm thick PA66 nylon white grey cloth is impregnated with the slurry material to make the amount of adhesive on the PA66 nylon white grey cloth reach 70 g / m 2 Then, the PA66 nylon white fabric is attached to the mold, which has a plurality of tooth-shaped grooves, and the PA66 nylon white fabric is attached to the mold surface on the side of the tooth-shaped groove opening; S2, 3 strands of glass fiber with a linear density of 135 g / 1000m are immersed in an RFL aqueous solution and then twisted into a glass core rope, the twist of the glass core rope is 140, and the tensile strength of a single glass core rope is greater than 80 N. The multiple glass core ropes are wound on the wrapping material described in step S1, and the rubber material prepared in Example 3 is wrapped on the glass core rope; S3. In the vulcanizing tank, the rubber material is compressed with 1 MPa high-pressure air, so that the rubber material penetrates the gap between the glass core ropes and stretches the PA66 nylon white fabric to enter the toothed groove of the mold to form a tooth layer and obtain a synchronous belt.

[0055] The tensile strength of the synchronous belt obtained in Example 4 is 669 N and the surface resistivity is 2×10 4Ω·m, the synchronous belt was applied to the RM / KR-9600 computer ophthalmometer. After 35,000 lifting and lowering tests, the synchronous belt was in good condition and could meet the service life requirement of 8-10 years.

[0056] Example 5

[0057] The present embodiment provides a rubber material, wherein the raw materials include the following components in parts by weight: 100 parts of chloroprene rubber, 0.1 parts of butadiene rubber, 9 parts of scorch retarder, 51 parts of reinforcing agent, 0.2 parts of accelerator, 3 parts of antioxidant, 6 parts of dispersant, 5 parts of plasticizer, 6 parts of crosslinking agent and 4.5 parts of tackifier; the scorch retarder is a layered double metal hydroxide; the accelerator is 3-methyl-2-thiazolethione; the plasticizer is dioctyl sebacate and oligomeric ester, and the mass ratio of dioctyl sebacate to oligomeric ester is 1:3; the antioxidant is 4 ,4'-dioctyldiphenylamine; the reinforcing agent is carbon black, multi-walled carbon nanotubes and precipitated silica, and the mass ratio of carbon black, multi-walled carbon nanotubes and precipitated silica is 50:5:4.5; the dispersant is a surfactant, a fatty acid soap and polyvinyl alcohol, and the mass ratio of the surfactant, fatty acid soap and polyvinyl alcohol is 1:5:3; the cross-linking agent is zinc oxide; the tackifier is hexamethylolamine hexamethyl ether and coumarone resin, and the mass ratio of hexamethylolamine hexamethyl ether and coumarone resin is 1:4.

[0058] It is prepared by the following preparation method: F1, 100 parts of chloroprene rubber were masticated for 210 s on an open mill with a roll gap of 2 mm, and 0.1 parts of cis-1,4-butadiene rubber were masticated for 30 s on an open mill with a roll gap of 2 mm, and the masticated chloroprene rubber and cis-1,4-butadiene rubber were mixed and masticated for a second time for 150 s to obtain a mixed masticated rubber; F2, the mixed plasticized rubber obtained in step F1 is added to an internal mixer, the rotor speed of the internal mixer is set to 30 r / min, 6 parts of dispersant, 5 parts of plasticizer and 9 parts of anti-scorch agent are added to perform a primary mixing for 150 s, the rotor speed of the internal mixer is set to 35 r / min, 51 parts of reinforcing agent are added to perform a secondary mixing for 150 s, and then the mixture is discharged at a temperature of 100°C, and then cooled with cooling water at 25°C, and kept at 25°C for 20 h to obtain a masterbatch; F3, the first-stage masterbatch obtained in step F2 is added to the internal mixer again, the rotor speed of the internal mixer is set to 30-35r / min, and then 3 parts of antioxidant, 0.5 parts of accelerator, 6 parts of cross-linking agent and 4.5 parts of tackifier are added and mixed for 70 s. After mixing, the glue is discharged at 100°C, and then it is quickly cooled by cooling water at 25°C, and then kept at 25°C for 20 h to obtain the second-stage masterbatch; F4. Add the second-stage masterbatch obtained in step F3 into an extruder to extrude an extruded rubber sheet. The extrusion speed of the extruder is 5.3 r / min. The thickness of the extruded rubber sheet is 0.65 mm. Then, after standing at room temperature for 30 hours, the extruded rubber sheet is vulcanized at a temperature of 160°C, a pressure of 5 MPa, and a time of 28 min to obtain a rubber material.

[0059] The tensile strength of the rubber material obtained in Example 5 is 16.2 MPa.

[0060] Example 6

[0061] The present embodiment provides a synchronous belt, which includes a rubber layer, a strength layer, a tooth rubber layer and a cloth covering layer, wherein the rubber layer and the tooth rubber layer are made of the rubber material prepared in Example 5, the thickness of the synchronous belt is 1.14±0.2 mm, the width is 6.3±0.2 mm, and the pitch line length of the synchronous belt is 186.944±0.4 mm.

[0062] It is prepared by the following preparation method: S1. The rubber material prepared in Example 5 is dissolved in toluene to obtain a slurry material. A 0.3 mm thick PA66 nylon white grey cloth is impregnated with the slurry material to make the amount of adhesive on the PA66 nylon white grey cloth reach 80 g / m 2 Then, the PA66 nylon white fabric is attached to the mold, which has a plurality of tooth-shaped grooves, and the PA66 nylon white fabric is attached to the mold surface on the side of the tooth-shaped groove opening; S2, 3 strands of glass fiber with a linear density of 120 g / 1000m are immersed in an RFL aqueous solution and then twisted into a glass core rope, the twist of the glass core rope is 160, and the tensile strength of a single glass core rope is greater than 80 N. The multiple glass core ropes are wound around the PA66 nylon white fabric prepared in step S1, and the rubber material prepared in Example 5 is attached to the glass core rope; S3. In the vulcanizing tank, the rubber material is compressed with 1.6 MPa high-pressure air, so that the rubber material penetrates the gap between the glass core ropes and stretches the PA66 nylon white fabric to enter the toothed groove of the mold to form a tooth layer and obtain a synchronous belt.

[0063] The tensile strength of the synchronous belt obtained in Example 6 is 672 N and the surface resistivity is 1×10 4 Ω·m, the synchronous belt was applied to the RM / KR-9600 computer ophthalmometer. After 35,000 lifting and lowering tests, the synchronous belt was in good condition and could meet the service life requirement of 8-10 years.

Claims

1. A rubber material, characterized in that: The raw materials of the rubber material include the following components in parts by mass: 95-100 parts of chloroprene rubber, 0.1-5 parts of butadiene rubber, 6-9 parts of scorch retarder, 51-63 parts of reinforcing agent, 0.2-0.5 parts of accelerator, 3-5 parts of antioxidant, 4-6 parts of dispersant, 5-7 parts of plasticizer, 4-6 parts of crosslinking agent and 4.5-6 parts of tackifier, the accelerator includes 3-methyl-2-thiazolethione, the plasticizer includes dioctyl sebacate and oligomeric esters, the antioxidant includes 4,4'-dioctyldiphenylamine, the reinforcing agent includes carbon black, multi-walled carbon nanotubes and precipitated silica, and the tackifier includes hexahydroxymethylmelamine hexamethylene ether and coumarone resin.

2. The rubber material according to claim 1, characterized in that: The mass ratio of the dioctyl sebacate to the oligomeric ester in the plasticizer is 1:(1-3); And / or, the mass ratio of the carbon black, the multi-walled carbon nanotubes and the precipitated silica in the reinforcing agent is (50-58):(1-5):(4.5-6); And / or, the mass ratio of the hexahydroxymethyl melamine hexamethylene ether to the coumarone resin in the tackifier is 1:(1-4); and / or, the scorch retarder comprises one or more of magnesium oxide and layered double metal hydroxide; and / or, the accelerator comprises 3-methyl-2-thiazolethione; and / or, the dispersant comprises a surfactant, a fatty acid soap and polyvinyl alcohol; And / or, the cross-linking agent comprises zinc oxide.

3. A method for preparing the rubber material according to claim 1 or 2, characterized in that: The following steps are involved: F1, chloroprene rubber and butadiene rubber are plasticized to obtain a mixed plasticized rubber; F2, adding a dispersant, a plasticizer, a scorch retarder and a reinforcing agent to the mixed plasticized rubber in step F1, mixing and draining the rubber, wherein the plasticizer includes dioctyl sebacate and oligomeric esters, and the reinforcing agent includes carbon black, multi-walled carbon nanotubes and precipitated silica, to obtain a masterbatch; F3, in step F2, an antioxidant, an accelerator, a crosslinking agent and a tackifier are added to the first-stage masterbatch and mixed, and the rubber is discharged after the mixing is completed, the accelerator includes 3-methyl-2-thiazolethione, and the tackifier includes hexahydroxymethyl melamine hexamethyl ether and coumarone resin to obtain a second-stage masterbatch; F4. Extruding the second-stage masterbatch in step F3 to obtain an extruded rubber sheet, and vulcanizing the extruded rubber sheet to obtain a rubber material.

4. The method for preparing the rubber material according to claim 3, characterized in that: In the step F1, the specific process of mastication is that the chloroprene rubber and the butadiene rubber are masticated once on an open mill respectively, and then the masticated chloroprene rubber and butadiene rubber are mixed, and masticated twice to obtain a mixed masticated rubber; And / or, in step F2, the mixing process is to add the mixed plasticized rubber obtained in step F1 into an internal mixer, then add a dispersant, a plasticizer and a scorch retarder for a first mixing, then add a reinforcing agent for a second mixing and then discharge the rubber, and then cool it with cooling water and keep it warm to obtain a masterbatch; And / or, in the step F3, the mixing process is to add the first-stage masterbatch after being kept warm in the step F2 into the internal mixer again, and then add the antioxidant, accelerator, cross-linking agent and tackifier and mix them, after the mixing is completed, discharge the glue, and then cool it with cooling water and keep it warm to obtain the second-stage masterbatch.

5. The method for preparing the rubber material according to claim 4, characterized in that: In step S1, the first mastication time of the chloroprene rubber is 180-210 s, the first mastication time of the butadiene rubber is 30-60 s, and the second mastication time is 120-150 s; And / or, in step S2, the rotor speed of the internal mixer is 30-35 r / min, the time of the first mixing is 120-150 s, the time of the second mixing is 120-150 s, and the temperature of the debinding is 100-120°C; And / or, in step S3, during the mixing, the speed of the internal mixer is 30-35 r / min, the mixing time is 70-90 s, and the debinding temperature is 90-100 °C; And / or, in step S4, the extrusion speed is 3.7-5.3 r / min, the thickness of the extruded film is 0.65-0.75 mm, the vulcanization temperature is 160° C., the pressure is 5-10 Mpa, and the time is 28-35 min.

6. A synchronous belt, characterized in that: The synchronous belt comprises a rubber layer, a strength layer, a tooth rubber layer and a cloth covering layer, and the rubber layer and the tooth rubber layer are prepared from the rubber material according to claim 1 or 2.

7. The synchronous belt according to claim 6, characterized in that: The synchronous belt has a thickness of 1.14±0.2 mm and a width of 6.3±0.2 mm; And / or, the pitch line length of the synchronous belt is 186.944±0.4 mm.

8. A method for preparing a synchronous belt as claimed in claim 6, characterized in that: The following steps are involved: S1, the elastic cloth material is impregnated with glue and then attached to a mold, the mold has a plurality of tooth-shaped grooves, and the elastic cloth material is attached to the mold surface on one side of the opening of the tooth-shaped grooves; S2, after impregnation, the glass fibers are twisted again to obtain a glass core rope, a plurality of the glass core ropes are wound around the elastic wrapping material of step S1, and the rubber material as claimed in claim 1 or 2 is wrapped around the glass core rope; S3, pressing the rubber material so that the rubber material penetrates the glass core rope and stretches the elastic cloth material to enter the toothed groove of the mold to form the synchronous belt.

9. The method for preparing a synchronous belt according to claim 8, characterized in that: The slurry material for the slurry impregnation in step S1 is a slurry obtained by dissolving the rubber material as claimed in claim 1 or 2 in toluene, and the amount of adhesive attached to the elastic wrapping material after the slurry impregnation is 70-80 g / m 2 ; And / or, the stretch wrapping fabric material in step S1 is nylon white grey fabric; And / or, in step S2, the strand density of the glass fiber is 120-135 g / 1000 m, the number of strands of the glass fiber is 3, and the impregnating solution is RFL impregnation solution; And / or, the twist of the glass core rope in step S2 is 140-160, and the tensile strength of a single glass core rope is greater than 80N; and / or, the pressing pressure in step S3 is 1-1.6 Mpa.

10. Use of the synchronous belt as claimed in claim 6 in a computer optometry instrument.